From the Other Shore: Exploring Home and Spatial Duality in Leïla Sebbar’s Le silence des rives (Silence on the Shores) - Nassima Amirouche (Literatūra (Vilnius))
The duality of here and there is a recurring motif in Maghrebian exile literature, which revolves around the experiences of North African immigrants who reside in Europe. This dualistic framework underscores the sense of displacement and cultural alienation that many immigrants experience in their new homes, as they find themselves straddling two cultures and struggling to find a sense of belonging in either of them. Leïla Sebbar’s novel Le silence des rives portrays the last day in the life of a Maghrebian immigrant in France, whose life is fraught with unfulfilled promises and shattered dreams. The present article examines how spatial duality and the here-there dichotomy serve as the main device for the exploration of the lives of the novel’s characters. This article also highlights the argument that the notions of “home” and “belonging” are not merely physical, but also emotional and psychological. The concept of spatial duality, as developed by Gaston Bachelard, provides a valuable framework for understanding the intricate relationship between exiles’ experiences of physical and psychological space. The postcolonial reading perspective also elucidates the complexity of (im)migrant subjectivity and the discourse of belonging.